You've been given the values of x. To find y, just substitute just in the value of x into the function. The initial equation is
![y = - {2x}^(2) * 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cc9jl3tw10ypa37n299zcjmjhvlg001t8j.png)
Therefore, for each value of x, anywhere you see x in the above function, just replace the value given with it.
The first one
![{ - 2 * ( - 2)}^(2) * 3 = y\\ \\ since \: - {2x}^(2) * 3 = y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zsyp44t40zi8q3h4dp3ssgipo73kyvxysr.png)
Simplify:
-2 × 4 × 3 = y
-8 × 3 = y
-24 = y
(x, y) = (-2,-24)
The second one
-2 × (-1^2) × 3 = y
-2 × 1 × 3 = y
-6 = y
(x, y) = (-1, - 6)
The third one
-2 × (0^2) × 3 = y
-2 × 0 × 3 = y
0 = y
The fourth one
-2 × (1^2) × 3 = y
-2 × 1 × 3 = y
-6 = y
The fifth one
-2 × (2^2) × 3 = y
-2 × 4 × 3 = y
-24 = y
Hence, the difference (if you plot those) is that you'll get a 'U' shape (also called a parabola). In the other, you'll get a straight line.